The intention to prevent sexual risk behaviors among the youth in Yangon, Myanmar - Ann Jirapongsuwan; Sithu Swe; Arpaporn Powwattana (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of this paper is to investigate the intention to prevent sexual risk behaviors and associated factors among the youth in Yangon, Myanmar. Design/methodology/approach - A cross-sectional descriptive research was undertaken among 192 youths. Participants included the youth residing in the study area and participated in the youth development program. Bivariate and multivariate logistic regressions were applied to identify an association. Findings - The findings indicated that the proportion of a high level of intention to prevent sexual risk behaviors was 53.6%. The factors associated with the intention to prevent sexual risk behaviors were: belief strength on sexual risk behaviors (aOR = 2.84; 95% CI: 1.06-7.26), normative belief on the prevention of sexual risk behaviors (aOR = 2.03; 95% CI: 3.03-6.23), motivation to comply with preventing sexual risk behaviors (aOR = 4.72; 95% CI: 3.11-6.23), decision-making (aOR = 2.46; 95% CI: 2.22-5.41) and negotiation (aOR = 6.3; 95% CI: 2.37-10.23) Research limitations/implications - The study was a cross-sectional study and cannot establish causal relationships. These results can be a guideline for implementation for the youth but may limit the generalization of results to other age groups in Myanmar. Practical implications - Findings can be used as a local and national public health guideline for developing interventions to prevent sexual risk behaviors. Originality/value - Sexual risk behavior is considered taboo and puts Myanmar youths at risk of health and social problems. It is important for prevention efforts to determine factors related to sexual intentions to prevent the consequence of these problems.